Optical Visualization of Red-GQDs’ Organelles Distribution and Localization in Living Cells - Hu, Haifeng; Li, Peng; Qiu, Jie; Zhao, Meiji; Kuang, Mingjie; Zhang, Zhaoyan; Wang, Dachuan (Frontiers in Pharmacology, 2022)
Recently, there has been a rapidly expanding interest in a new nanomaterial, graphene quantum dots (GQDs), owing to its profound potential in various advanced applications. At present, the study of GQDs mainly focuses on the new synthesis methods and surface modification. However, revealing the intracellular distribution of GQDs is currently not available, limiting in-depth understanding of its biological regulatory mechanism. To fill up this gap, the visualization study of red fluorescent graphene quantum dots (Red-GQDs) is helpful to clarify their subcellular distribution and metabolism in living cells system. Here, in this study, two-photon laser confocal microscopy was used to deeply analyze the uptake and subcellular distribution of Red-GQDs by HeLa cells at different concentrations and times through visual observation and discussed the effect of Red-GQDs on the metabolic of HeLa cells. The results indicated that Red-GQDs could be well-absorbed by HeLa cells and further revealed the differential distribution of Red-GQDs in different organelles (lysosomes and mitochondria) in a time-dependent manner. In addition, we confirmed that Red-GQDs significantly affect cell biological functions. Low concentrations of Red-GQDs are related to the autophagy pathway of cells, and high concentrations of Red-GQDs can induce ferroptosis in cells and promote the secretion of cellular exosomes. In the present study, the distribution and metabolic pathways of Red-GQDs in the subcellular structure of cells were characterized in detail through visual analysis, which can bring positive reference for the application of Red-GQDs in the future.